Pneumococcal carriage in children with COVID-19. Issue 6 (3rd June 2021) - Aykac, Kubra; Ozsurekci, Yasemin; Cura Yayla, Burcu Ceylan; Evren, Kubra; Lacinel Gurlevik, Sibel; Oygar, Pembe Derin; Yucel, Mihriban; Karakoc, Ayse Esra; Alp, Alpaslan; Cengiz, Ali Bulent; Ceyhan, Mehmet
ABSTRACT: Background : SARS-CoV-2 is the new virus, and Streptococcus pneumoniae is one of the most important pathogens affecting humans. However, we do not yet know whether these microorganisms interact. Thus, we aimed to evaluate the relationship between Streptococcus pneumoniae and SARS-CoV-2 in pediatric patients. Methods : This study was conducted retrospectively by means of medical records of pediatric patients who were tested for SARS-CoV-2 between March 11 and June 04, 2020, in the University of Health Sciences, Ankara Educating and Training Hospital and Hacettepe University Faculty of Medicine. Results : We evaluated 829 pediatric patients for S. pneumoniae and SARS-CoV-2 from their nasopharyngeal specimen. Of 115 children positive for SARS-CoV-2, 32.2% had a positive S. pneumoniae test, whereas of 714 children negative for SARS-CoV-2, 14.1% had a positive S. pneumoniae test ( p < .01). We compared patients with positive vs. negative SARS-CoV-2 tests according to S. pneumoniae positivity There were no statistically significant differences in terms of gender, underlying disease, fever, cough, leukocytosis, lymphopenia, increased CRP, increased procalcitonin, findings of chest x-ray, severity of disease, and treatment. Conclusion : The nasopharyngeal S. pneumoniae carriage rate in patients with COVID-19 was higher than in non-infected children, while S. pneumoniae carriage did not affect the course of COVID-19 disease. Pneumococcal vaccination is significant, such that we do not know the outcomes of increased pneumococcal carriage for the upcoming months of pandemic.